2016
DOI: 10.1108/jabs-06-2014-0043
|View full text |Cite
|
Sign up to set email alerts
|

Business relationship framework in Indonesia: relationship marketing vs transaction cost

Abstract: Purpose – This paper aims to explore business relationship framework between two companies. In this research, relationship marketing and transaction cost were used as frameworks to analyze business relationship of two different kinds of companies in Indonesia, oil company and hypermarket. Gronroos (1994) defines relationship marketing is establishing, maintaining and enhancing relationships with customers and other partners, at a profit, so that the objectives of the parties involved are met. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Two weeks after the initial mailing, reminder post cards were mailed to participants who had not returned their questionnaires. A total of 262 usable responses were returned, and a usable response rate of 26.2 per cent was considered acceptable when compared with similar studies on marketing channels (Kabadayi, 2011; Setyawan et al , 2016). Because this study focuses on firms that use dual channels, those that use single channels need to be excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Two weeks after the initial mailing, reminder post cards were mailed to participants who had not returned their questionnaires. A total of 262 usable responses were returned, and a usable response rate of 26.2 per cent was considered acceptable when compared with similar studies on marketing channels (Kabadayi, 2011; Setyawan et al , 2016). Because this study focuses on firms that use dual channels, those that use single channels need to be excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, SMEs are presumed to confront the strategy of their powerful partner, i.e., large companies. A preliminary study of the relationship marketing between SMEs and large companies in Indonesia found the occurrence of power asymmetry in this relationship (Setyawan et al, 2016).…”
Section: Figure 1 Research Modelmentioning
confidence: 99%
“…They found that trust and formal control complement each other in the context of weak ties and that trust is more effective in strong ties. In Indonesia, Setyawan et al (2016) asserted that the nature of the supplier–purchaser relationship varies by industry with the oil industry using strict contracts, whereas the retail industry relies on personal trust grounded in long-term relationships. Finally, in the context of R&D strategic alliances, Schilke and Cook (2013) found that reputation determines the type of trust employed with firms using a calculative contractual trust when forming alliances with low-reputation firms and a relational trust when forming alliances with high-reputation firms.…”
Section: Theoretical Overviewmentioning
confidence: 99%